Análise da microconformação do alumínio de grãos ultrafinos - Moraes, Etiane Carvalho (Universidade Federal de São Carlos, 2018)
Product miniaturization is a current trend, involving several industry segments. Microforming is an especially interesting process to produce parts in millimeter scale because of its high productivity. The grain size can be considered as a key micro structural factor for downsizing the deformation process because it affects almost all physical and mechanical behavior of polycrystalline metals. Ultrafine grain material shows a great potential for microforming since they can decrease the elastic and plastic anisotropy that would prevail in a coarse grain structure. The aim of the study is to compare the conformability of coarse and ultrafine grain structures of a commercial grade aluminum (ASTM AA1050) in the deep drawing process at different scales to ckeck the increase in the quality of the miniaturized product and process. The material, originated from a 7 mm roll-casted sheet, was solutionized at 400°C for 2h producing a coarse grain structure of an average grain size of 150µm (CG material). The production of ultrafine grain samples was carried out by Equal-channel angular pressing (ECAP) using a die with an internal angle of 120°C, and route A (no rotation of the samples between passes) up to 8 passes, achieving an average grain size of 1,5µm (FG material). The grain size effect was analyzed by microhardness and tensile tests. In order to get an effective comparison between differences in dimensional scales and grain sizes, the scalar comparison was performed in four effective volumes: 252mm3, 42mm3, 28mm3 and 1mm3 in tensile experiments performed at a strain rate of 10−3 s −1. The traction test was also performed by the virtual field method (VFM), to verify the behavior of the material in the of the in the necking region. The deformation pattern was characterized by electron backscatter diffraction (EBSD) and microhardness tests and scanning electron microscopy. A drawing die was designed to evaluate the behavior of these two materials with sheet thickness of 1 and 0.5 mm. The two materials had different deformation mechanisms: in CG the strain concentrated inside the grains and new interfaces were created with continuous hardening in the neck region, whereas in FG the thickness of the existent boundaries increased and strain was promoted by grain boundary sliding, which yield softening in the neck region. The CG structure yield larger uniform elongation and deeper drawing rate than the FG structure. On the other hand, the form adjustment and strain distribution was more uniform in the FG material than in the CG material. Contrary to the expected from the literature review, an increase of the deformation stress was measured when the scale of the sample was reduced. This effect was more accentuated in the FG than in the CG material, and this behavioral was associated to the increment of the relative sample volume participating in the stress concentration at the reduced scale.
Analysis of microforming of ultrafine grain aluminum
Keywords: Deformação plástica severa; Grãos ultrafinos; Miniaturização; Severe plastic deformation; Ultrafine grain; Miniaturization; Estampagem (Metais); Metal stamping; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS::MECANICA DOS CORPOS SOLIDOS, ELASTICOS E PLASTICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO::CONFORMACAO MECANICA